Tacrolimus Pharmacotherapy: Infectious Complications and Toxicity in Organ Transplant Recipients; An Updated Review - Tolou-Ghamari, Zahra; Palizban, Abbas-Ali (Current Drug Research Reviews, 2025)
BackgroundAfter allogeneic organ transplantation, in order to reduce the risk of rejection, tacrolimus is given. In fact, infection is reported as one of the most common side effects of tacrolimus that might be associated with graft failure.ObjectivesThis study aims to review the association between the occurrence of infections due to toxicity following the administration of tacrolimus in organ transplant recipients.MethodsScientific literature on the pharmacotherapy of tacrolimus after organ transplantation, infections, and neurotoxicity were searched using PUBMED.Gov (https://pubmed.ncbi.nlm.nih.gov/), Web of Science, and Scopus (n=108). All articles were screened, and the data associated with the topic of interest was extracted. The primary outcome was infection and neurotoxicity.ResultsTotal area under the curve exposure, the ratio of parent drug/metabolites of tacrolimus was reported to be correlated with aggressive events such as infection episodes. A trough/dose ratio may demonstrate the net state of immunosuppression and drug-related events. The most frequent infectious complication of tacrolimus after organ transplantation was reported as urinary tract infections (UTIs). Virulent strains of recombinant Listeria monocytogenes, in addition to an increase in bacterial burden in the liver and spleen tissues, were reported in experimental animal studies. Patient survival was significantly lower in recipients with UTIs in the first post-transplant month. A higher degree of immunosuppression was associated with recurrent UTIs and drug-resistant organisms. By inhibiting the cerebral immune system, tacrolimus could cause neurodegeneration.ConclusionTransplant type, gut dysmotility, acute or chronic condition before transplant surgery, use of azole, antifungal, hematocrit, tacrolimus methods of detection, the total area under the curve, and duration of hospital stay could define the risk of infection through the first month of transplant surgery. In addition, neurological and infectious complications could be associated with the higher amounts of tacrolimus trough levels (C0). Polypharmacy based on tacrolimus, antiviral, and antifungal drugs, in addition to neurotoxicity, could increase the risk of opportunistic infections such as cytomegalovirus within the first year of organ transplantation.
Keywords: immunosuppressive